75.8k views
3 votes
What’s the steps
To this question I don’t know it

What’s the steps To this question I don’t know it-example-1
User Nullforce
by
5.2k points

2 Answers

3 votes
(0-((7•(x4))•(y2)))•(0-(2x3•y))

(0- (7x4 • y2)) • -2x3y

3.1 x4 multiplied by x3 = x(4+3)=x7

3.2 y2 multiplied by y1 = y (2+1) = y3

Final answer ••• (7•2x7y3)
User Laudy
by
5.7k points
5 votes

Answer:


(-7x^4y^2)(-2x^3y)\\=(-7)(x^4)(y^2)(-2)(x^3)(y)\\=(-7*-2)(x^4*x^3)(y^2*y)\\=(14)(x^7)(y^3)\\=14x^7y^3

User Scott Wylie
by
5.5k points